Simple extraction of bisphenol A in beverages and water by membrane-protected liquid phase microextraction - Loh, Thung Ying; Wan Mohd Afiq Wan Mohd Khalik; Loh, Saw Hong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bisphenol A (BPA) is a xenoestrogen that widely used in manufacture of plastics. Concern is mounting up when the application of BPA is widespread. A simple sample pre-treatment technique termed membrane-protected liquid phase microextraction (MP-LPME) combined with high performance liquid chromatography (HPLC)-fluorescence detection (FD) was developed for the determination of BPA in beverages and environmental water samples. The MP-LPME technique utilized a nylon membrane to hold the extractant (1-octanol) and prevent the extractant from dissolution into sample solution during agitation. Under optimal extraction conditions, the MP-LPME-HPLC-FD demonstrated ultra-trace detection of BPA and insignificant matrix effect extraction with good relative recoveries in the range of 87.1-99.7% from spiked beverage and environmental water samples. The membrane can be re-applied in the MP-LPME after the first usage and offered relative recovery of > 94%. The MP-LPME technique is eco-friendly as it consumes only minute amounts of organic solvent which is supportive to green analysis.